Forms of Gender Equality on Female Characters in Singkar Novels - Jefrianto, Jefrianto; Widayat, Afendy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the representation of gender equality through the characterization of female characters in the novel Singkar by Siti Aminah. Using a descriptive approach and feminist analysis framework, this research explores the forms of gender equality displayed by female characters and their relationship with the construction of their characters in the novel. The research data in the form of the entire text of the novel Singkar was analyzed through read-and-record techniques and descriptive analysis. Semantic validity and intraretter reliability were used to ensure data validity. The results showed five forms of gender equality expressed by female characters in the novel: 1) autonomy in making decisions, 2) ability to overcome problems, 3) courage to take responsibility, 4) participation in earning a living, and 5) resilience as a single parent. This finding confirms that the characterization of female characters in Singkar is the basis for actions that reflect gender equality.